Stylus Studio 6 from Progress Software an integrated tool with breadth. - Barbash, Brian (SOA webservices journal.)
XML Development - the term can mean many different things given the technologies currently available. At the center of it all is XML Schemas, DTDs and instance documents. Building out from the base there's XSL, Web Services and XQuery just to name a few. Because of this, it's not uncommon for a developer to have several tools, each specialized in one of those technologies. Stylus Studio, however, provides an integrated environment for XML development with broad support for the various technologies. This review covers its capabilities in some of the major areas.